Pengaruh Kebijakan Hutang dan Profitabilitas Terhadap Kebijakan Dividen (Study Pada Perusahaan Food and Beverage yang Terdaftar di BEI Tahun 2014-2016) - Nike Anggita Prima; Ronny Malavia Mardani; M Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
Dividend policy is a profit decision whether the profits to be obtained by the company at the end of the period will be distributed to shareholders or will be retained as retained earnings. Dividend policy in this study uses the Dividend Payout Ratio (DPR) formula. To see how the influence of debt and profitability policies on dividend policy on food and beverage companies listed on the Indonesia Stock Exchange in 2014-2016. The research used is a quantitative approach which includes the type of research exploratory research. The population in this study were 18 companies and a sample of 9 companies. The results of the analysis show that Debt and Profitability Policy influences the dividend policy on Food and Beverage Companies listed on the Stock Exchange in 2014-2016. Characteristics of food and beverage companies tend to finance companies by using debt for dividend distribution. Keywords: debt policy, profitability and dividend policy